Strategy for financial inclusion of informal economy workers - Seema Sharma; Arnab Bose; Himanshu Shekhar; Rohit Pathania (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Access to finance and financial inclusion has been identified as a key enabler in the modern society. It provides for basic economic security of the family and is instrumental in preventing families from falling back into poverty. The jan-dhan account in India has been a key milestone in this regard, providing access to every family virtually in the country with a formal bank account. But the bank account can only be the first step as financial inclusion in true sense would mean access to various financial schemes and services like credit and insurance, which remain the most crucial for the intended outcomes. Informality of jobs with non-regular un-recorded income becomes the biggest challenge for financial institutions to provide these services to a large section of the society. The informality of jobs may take various shapes and forms. Through this paper we identify the local static informal service providers which have been with any local community for more than two years across India or other emerging economies but may not have enough "formality" to access the financial services. In this paper we will discuss the reasons for such exclusion and a strategy involving a socio-technical transition which can make the intended transformation to financial inclusion of the static workers in the informal economy.
Keywords: J46; 330; Financial Inclusion; Informal workers; Street vendors; Urban Informal sector